DEVELOPMENT OF HIGH-QUALITY HUMAN RESOURCES SERVING FOR SOCIOECONOMIC DEVELOPMENT OF DA NANG CITY - Do Thi Hang Nga (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Da Nang city is a national grade I, dynamic city in the Central Viet Nam and Central Highlands, plays an important role in contributing to the successful implementation of industrialization and modernization of the country. Therefore, Da Nang City should have high quality human resources, in particular, those who are virtuous, talented, intelligent, creative, well-prepared in terms of cultural knowledge, well-trained in terms of professional skills, production capacity, economic and social management, and high scientific and technical level. Since the implementation of the high-quality human resource development project in 2004, undergoing many changes, the development of the high technology of Da Nang has partly met the requirements of the economic development process of the country in general and Da Nang in particular. Derived from this, the paper is to clarify some aspects of the theoretical issues of high-quality human resources that provide a scientific basis for analyzing the situation of Danang City and proposing solutions for developing the high-quality human resources of Danang City in the future.